2021
DOI: 10.48550/arxiv.2103.14651
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local Explanations via Necessity and Sufficiency: Unifying Theory and Practice

Abstract: Necessity and sufficiency are the building blocks of all successful explanations. Yet despite their importance, these notions have been conceptually underdeveloped and inconsistently applied in explainable artificial intelligence (XAI), a fastgrowing research area that is so far lacking in firm theoretical foundations. Building on work in logic, probability, and causality, we establish the central role of necessity and sufficiency in XAI, unifying seemingly disparate methods in a single formal framework. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…certa builds perturbed copies in a data-driven way, using sequences of tokens that come from the training set distribution and hence are more likely to be correctly classified by the ER system. Perturbed copies are used to compute saliency and counterfactual explanations according to the probabilistic framework developed in [36], which associates the former to the probability of necessity, and the latter to the probability of sufficiency.…”
Section: Foundations and Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…certa builds perturbed copies in a data-driven way, using sequences of tokens that come from the training set distribution and hence are more likely to be correctly classified by the ER system. Perturbed copies are used to compute saliency and counterfactual explanations according to the probabilistic framework developed in [36], which associates the former to the probability of necessity, and the latter to the probability of sufficiency.…”
Section: Foundations and Problem Statementmentioning
confidence: 99%
“…It has been observed that saliency and counterfactual explanation methods are different but complimentary methods to be used to best evaluate causality aspects of a classifier prediction [14]. Saliency methods align well with the notion of necessity, while counterfactual explanation methods align with the notion of sufficiency [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reverse causal inference. Our work is also related to a body of work on reverse causal inference, a task that aims to nd "causes of e ects" (Chalupka et al, 2017(Chalupka et al, , 2015Galhotra et al, 2021;Gelman & Imbens, 2013;Janzing & Schölkopf, 2015;Kilbertus et al, 2018;Kommiya Mothilal et al, 2021;Paul, 2017;Schölkopf et al, 2012Schölkopf et al, , 2013Wang & Culotta, 2020Watson et al, 2021;Weichwald et al, 2014). Existing approaches formulate the search for causes as causal hypotheses generation and testing.…”
Section: Unsupervisedmentioning
confidence: 99%
“…It has been observed that saliency and counterfactual explanation methods are different but complimentary methods to be used to best evaluate causality aspects of a classifier prediction [14]. Saliency methods align well with the notion of necessity, while counterfactual explanation methods align with the notion of sufficiency [37].…”
Section: Introductionmentioning
confidence: 99%